Kesiapan Kerja Melalui Efikasi Diri, Motivasi Kerja, Soft skill, dan Praktik Industri pada Mahasiswa Vokasi - Agus Ardiyanto; Ida Aryati Diyah; Supawi Pawenang (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Competition for jobs is getting higher because the number of job seekers is greater than the availability of job opportunities, resulting in increased unemployment. Tight competition in the world of work requires the work readiness of graduates from vocational colleges, to have expertise and skills in their fields and be ready to work. This study aims to analyse the effect of self-efficacy, work motivation, soft skills and industrial practice on work readiness in AK-Tekstil Solo vocational students. This study uses a quantitative descriptive approach. The sampling technique was saturated sampling with a sample of 97 students of class 2023 AK-Tekstil Solo. The data analysis technique uses statistical analysis, namely multiple linear regression tests, T tests, F tests, and coefficients of determination. The results showed that self-efficacy, soft skill work motivation, industrial practice had a positive and significant effect on student work readiness. Self-efficacy, work motivation, soft skills, and industrial practice have a significant and simultaneous effect of 93.4% on the work readiness of AK-Tekstil Solo vocational students. Thus increasing self-efficacy, work motivation, soft skills, and industrial practice will increase the work readiness of AK-Tekstil Solo vocational students.